Analysis of Excess Inventory Management Using Reverse Logistics in the Electronics Sector: (A Case Study on SADES Indonesia) - Stephanny Lianardo; Maulibian Perdana Putra; Steven (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2025)
Rapid changes in trends and technological developments play a role in changes related to market demand. Often, a product line must be discontinued early due to sudden changes or shifts resulting from the emergence of new technological developments or new technological standards. Demand for newer models forces companies to launch new product lines and discontinue distribution or sales of existing ones. This phenomenon results in excess stock that ultimately leads to stagnation in warehouse inventory turnover, where this stagnant inventory storage causes additional costs for the company or becomes waste, and the company also experiences losses from this unsold inventory. This study aims to analyze the implementation of strategies and actions taken by companies, distributors, and retailers using a case study method to analyze best practices in managing end-of-cycle inventory for the company's sustainability and profitability. The findings in this research reveal that the implementation of reverse logistics in the retail of electronic industry has developed into an adaptive and dynamic system in which the continuous flow of information from the secondary market from the reverse logistics implementation drives and influence the change and the transformation on how the operational division identify, classify, and making decision on their excess inventories and dead stock moving forward.